2021
DOI: 10.3389/fonc.2021.637049
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Versus Conventional Nipple-Sparing Mastectomy With Immediate Breast Reconstruction

Abstract: BackgroundSeveral studies reported the feasibility and safety of robotic-NSM (R-NSM). The aim of our prospective study was to compare R-NSM and conventional-NSM (C-NSM).MethodsWe analyzed patients who were operated on with and without robotic assistance (R-NSM or C-NSM) and who received immediate breast reconstruction (IBR) with implant or latissimus dorsi-flap (LDF). The main objective was complication rate and secondary aims were post-operative length of hospitalization (POLH), duration of surgery, and cost.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…In the current study, the overall medical costs of R-NSM were ~4000 USDs more than C-NSM and 2600 USDs more than E-NSM (Supplemental Digital Content Table 3, http://links.lww.com/SLA/E624). These findings were consistent with one study that reported an extra 1749 Euros for R-NSM compared with C-NSM 24 . Increased costs from R-NSM have been one of the most important rate-limiting factors for its widespread adoption 15 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the current study, the overall medical costs of R-NSM were ~4000 USDs more than C-NSM and 2600 USDs more than E-NSM (Supplemental Digital Content Table 3, http://links.lww.com/SLA/E624). These findings were consistent with one study that reported an extra 1749 Euros for R-NSM compared with C-NSM 24 . Increased costs from R-NSM have been one of the most important rate-limiting factors for its widespread adoption 15 .…”
Section: Discussionsupporting
confidence: 90%
“…com/SLA/E624). These results were comparable to those of reported case studies, 12,23,24,35 meta-analyses, 27 and RCT. 29 In our study, a higher C-D classification grade 3 complication rate was noted in the C-NSM (13.7%) group than in the E-NSM (4.8%) and R-NSM (2.6%, P = 0.02, Supplemental Digital Content Table 2, http://links.lww.com/SLA/E624) groups.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…9,20,39,40,42,45,[51][52][53][54] Comparison studies between R-NSM, E-NSM, and open NSM have shown that R-NSM takes longer than either E-NSM or open NSM on average; however, other studies have shown that after 10 to 12 attempts, total operative time for R-NSM was similar to open NSM. 38,45,55,56 Perioperative complications are similar for NSM, regardless of the technique used. Most studies on R-NSM reported outcomes including major complications (reoperation, implant loss, and conversion to open technique), minor complications (transient neuropathy, hematoma, seroma, thermal injury, eschar formation, mastectomy flap, or NAC necrosis), postoperative pain, and hospital length of stay.…”
Section: Discussionmentioning
confidence: 98%
“…In studies comparing R-NSM to either E-NSM or open NSM, no significant differences in overall complication rates were observed. 38,55,56 When assessing the complication profiles for R-NSM, it is important to note that all studies included various additional reconstructive procedures (e.g., direct to implant reconstruction, tissue expander placement, latissimus dorsi harvest, and contralateral symmetrizing procedures) which can make it difficult to determine specifically whether the complication is attributed to the R-NSM procedure itself or the associated procedures. Since R-NSM is an emerging technique with relatively short follow-up, there is a paucity of data on oncological outcomes for breast surgery patients undergoing this procedure.…”
Section: Discussionmentioning
confidence: 99%